1994
DOI: 10.1136/bjo.78.7.529
|View full text |Cite
|
Sign up to set email alerts
|

Acute angle closure glaucoma: relative failure of YAG iridotomy in affected eyes and factors influencing outcome.

Abstract: The treatment ofacute angle closure glaucoma has been influenced by the development of the YAG laser and its ability to perform iridotomies as an outpatient procedure. In this retrospective study the results of YAG iridotomy were compared with surgical peripheral iridectomy. When compared with surgical peripheral iridectomy patients, YAG iridotomy patients were at greater risk of proceeding to further surgery, with this risk being significantly associated with increasing duration of attack. The authors suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 13 publications
1
24
0
1
Order By: Relevance
“…The results of this study, and previous retrospective studies,8 9 suggest that Nd:YAG laser iridotomy is a satisfactory alternative to operative iridectomy in the treatment of AACG eyes. However, in view of the relatively small number of patients in our study, and the inherently unsatisfactory nature of retrospective studies of this disease,7-9 doubt must persist as to which treatment is optimal 16.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The results of this study, and previous retrospective studies,8 9 suggest that Nd:YAG laser iridotomy is a satisfactory alternative to operative iridectomy in the treatment of AACG eyes. However, in view of the relatively small number of patients in our study, and the inherently unsatisfactory nature of retrospective studies of this disease,7-9 doubt must persist as to which treatment is optimal 16.…”
Section: Discussionsupporting
confidence: 62%
“…While there was a trend towards worsening acuity with time in both groups, presumably because of age related lens changes, there was no significant change in visual acuity after 3 years compared with either visual acuity following initial medical control or visual acuity 2 months following treatment. Buckley et al , in a retrospective study, found no significant difference in visual acuity outcome following operative iridectomy or laser iridotomy 8. In their study visual acuity in the fellow eye at presentation was used as an assumption of the visual acuity in the affected eye before the episode of AACG.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The indications of initial trabeculectomy in PACG were an inability to control the IOP on presentation [8,16,17] and advanced optic disk changes with the presence of PAS covering more than 75% of the trabular meshwork [18,19], We believe that there arc some racial differences in manifestations and managements of PACG between Caucasians and Orientals. The Asian pa tients frequently fail to present until permanently reduced vision is noted during the progression, and iridotomy alone may be insufficient to cure the glaucoma [6].…”
Section: Discussionmentioning
confidence: 99%
“…Playfair and Watson 6 and Krupin et al 7 reported that controlled IOP was achieved with surgical PI or LPI alone in 72% and 76% of eyes, respectively, and with antiglaucoma agents in 84% and 96% of eyes, respectively. In 137 APAC patients who underwent LPI or surgical PI as a primary treatment, Buckley et al 17 showed that good IOP was maintained in 80 eyes (58.4%) that required no further medications, while 21 eyes (15.3%) ultimately required trabeculectomy. A recent study from the United Kingdom 18 found that no additional treatment after LPI was required in 44% of cases, and that further medical or surgical intervention was required in 21% and 35% of cases, respectively.…”
Section: Meds (+) (3) No Meds (30) Meds (+) (20)mentioning
confidence: 98%